Chemical Changes in Alluvial Lawn Soils, Fertilized by Sediments from Wastewater Treatment Stations - Marinova, Svetla; Tsolova, V.; Kathijotes, Nicholas (My University, 2005)
Large amounts of sludge which are produced from biological treatment of wastewater are expected to be placed at a variety of appropriate locations of disposal. Research shows that sludge containing biomass, rich in macro and microelements, may substitute our organic matter reserves, considering the shortages of these reserves in our country. Research has also shown the effect and possibility of the use of this resource on soils (Marinova 2002, Kasatikov 1984). The important question to be resolved is their ecological effects on soils when applied as fertilizers or soil conditioners. The aim of this research paper is to evaluate the chemical changes in alluvial field soils, as applied after intensive and continuous application to such soils.
Keywords: Wastewater sludge; Alluvial soils; Sludge disposal; Sludge application; Wastewater sludge; Alluvial soils; Sludge disposal; Sludge application